Recent Developments in the Synthesis of β-Diketones - Gonzalo de Gonzalo; Andrés R. Alcántara (MDPI AG, 2021)
Apart from being one of the most important intermediates in chemical synthesis, broadly used in the formation of C-C bonds among other processes, the β-dicarbonyl structure is present in a huge number of biologically and pharmaceutically active compounds. In fact, mainly derived from the well-known antioxidant capability associated with the corresponding enol tautomer, β-diketones are valuable compounds in the treatment of many pathological disorders, such as cardiovascular and liver diseases, hypertension, obesity, diabetes, neurological disorders, inflammation, skin diseases, fibrosis, or arthritis; therefore, the synthesis of these structures is an area of overwhelming interest for organic chemists. This paper is devoted to the advances achieved in the last ten years for the preparation of 1,3-diketones, using different chemical (Claisen, hydration of alkynones, decarboxylative coupling) or catalytic (biocatalysis, organocatalytic, metal-based catalysis) methodologies: Additionally, the preparation of branched β-dicarbonyl compounds by means of α-functionalization of non-substituted 1,3-diketones are also discussed.